Primates of the world : an illustrated guide - Petter, Jean-Jacques; Desbordes, François (Princeton University Press, 2013)
This stunningly illustrated guide to the world's primates covers nearly 300 species, from the feather-light and solitary pygmy mouse lemurs of Madagascar--among the smallest primates known to exist--to the regal mountain gorillas of Africa. Organized by region and spanning every family of primates on Earth, the book features 72 splendid color plates, facing-page descriptions of key features of each family, and 86 color distribution maps.